Art and Politics in Antioquia - Gutiérrez Gómez, Alba Cecilia (Estudios de Filosofía, 2018)
During the thirties and the forties, an Americanist and Nationalist Art, with an evident social character, was developed in Antioquia. Pedro Nel Gómez, Carlos Correa and Débora Arango were among the main representatives. This paper addresses the theoretical discussions between those people inpro of Mexican Muralism and those in pro o fa Modern International Art, as opposed to any ideological contents, headed in Colombia by the critic ofArt Marta Traba. This paper will consider the discussion in three steps: the climatic years of social Art (1934-1950), its crisis (1950-1960) and the current revision of Art history in Colombia.